ANALISIS PENGARUH LOVE OF MONEY, GENDER, RELIGIUS TERHADAP PERSEPSI ETIS MAHASISWA AKUNTANSI (Studi Kasus di satu PTN dan dua PTS di Malang) - Firdausia Oktaviana; Maslichah Maslichah; M. Cholid Mawardi (Universitas Islam Malang, 2018)
ABSTRACTThis study aims to analyze whether there is a relationship between love of money,and level of religiousity on ethical perception of accounting students. It also aims tofind out if there are differences in the level of religiosity , the of love money and ethicalperceptions of accounting students based on gender. The data from questionnaire are170 and this study used structure equition modelling (SEM) with software AMOS.The results of this study shown: that gender variables are not influence to the loveof money, religiousity and ethical perceptions of accounting students, love of money andreligiousity variables influence the perception of accounting students. The higher of thestudent’s love of money then lower level of their ethical perceptions will be. The higherdegree of religiosity of the students will be increasing the higher level of their ethicalperception.Keywords: Love of Money, gender, Religiousity, and Ethical Perception AccountingStudents